1978
DOI: 10.1042/bj1720015
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a proton/sugar symport in the yeast Rhodotorula gracilis (glutinis)

Abstract: 1. The uptake of monosaccharides and polyols in the obligatory aerobic yeast Rhodotorula gracilis (glutinis) was accompanied by proton uptake. 2. The halfsaturation constant of transport, KT, depended on pH, changing from about 2mM at pH4.5 to 80mM at pH8.5 for D-xylose; this change of the effective carrier affinity was reversible. 3. The apparent dissociation constant of the monosaccharide carrier was estimated at pKa 6.75. 4. At pH8.5, when the pH gradient across the cell membrane vanished, no sugar accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 22 publications
3
43
0
Order By: Relevance
“…Facilitated diffusion and proton-sugar symport have been established for many different types of yeast (8,16,19,20). Moreover, it is claimed that glucose transport in Saccharomyces cerevisiae and Kluyveromyces marxianus can proceed through a phosphotransferase (10,17).…”
mentioning
confidence: 99%
“…Facilitated diffusion and proton-sugar symport have been established for many different types of yeast (8,16,19,20). Moreover, it is claimed that glucose transport in Saccharomyces cerevisiae and Kluyveromyces marxianus can proceed through a phosphotransferase (10,17).…”
mentioning
confidence: 99%
“…S. cerevisiae (Eddy, 1978 ; Sigler et al, 198 l), Schizosaccharomyces pombe (Foury et al, 1977) and Rhodotorula glutinis (Hofer & Misra, 1978), glucose induced a strong acidification of M . reukauji cell suspensions (Fig.…”
Section: Efsect Of Glucose and Ethanol On H+ And K+jeuxes In Aerated mentioning
confidence: 99%
“…The obligatory aerobic yeast Rhodotorula glutinis is capable of transporting a wide variety of metabolizable and non-metabolizable monosaccharides by an electrogenic H+-symport (Hofer & Misra, 1978 ;Hauer & Hofer, 1978). Early results suggested that -the uptake of monosaccharides was mediated by a common membrane transport system, displaying a high substrate specificity for D-glucose (Kotyk & Hofer, 1965;Hofer & Kotyk, 1968;Hofer, 1970;Hofer & Dahle, 1972).…”
Section: Introductionmentioning
confidence: 99%